Developing Video-based Instructional Media for Clutch System Maintenance in Light Vehicle Chassis and Powertrain Learning - Sugeng Priyanto; Valent Adnandhiya Awalia (LPPM Institut Pendidikan Nusantara Global, 2024)
Learning media continues to develop and become an important component that supports the learning process because it can improve the quality of learning, help increase student engagement, and make lessons more accessible. The utilisa- tion of learning media still has some weaknesses such as not being able to display the original movement in practice and less interactive. These weaknesses can be overcome through media customisation and development. Quality education can be realised by changing conventional media into learning media that is more appropriate and easy to understand. This study aims to develop and design learning video media for clutch system maintenance subject matter in Light Ve- hicle Chassis and Powertrain Maintenance subjects according to material experts, media experts, and media feasibility tests on students. This research uses the Research and Development (R&D) method and uses the 4D development model. The results of the feasibility test of video-based learning media get a percentage of 95.29% from material expert valida- tors, 86.66% from media expert validators, and 88% from the results of the media feasibility test results of 30 students. From the test results, it can be concluded that the video-based learning media for clutch system maintenance subject matter in the Light Vehicle Chassis and Powertrain Maintenance subject is ‘Very Feasible’ to be used for learning activi- ties.